2018
DOI: 10.25258/phyto.v10i01.11929
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacognostic Evaluation of Curcuma longa L. Rhizome and Standardization of its Formulation by HPLC Using Curcumin as Marker

Abstract: Objective: To evaluate Curcuma longa rhizome by pharmacognostic and phytochemical analysis and standardize one of its formulations by HPLC. The present work includes macroscopic study, microscopic analysis of cross section and powder of rhizome, fluorescence analysis, qualitative and quantitative phytochemical assay and chromatographic fingerprinting of its polyherbal formulation, Pathyashadangam kwath using curcumin as marker carried out as per standard laboratory procedures. The study helps to provide both d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Increased boiling duration appears to have a greater impact on the total ash content in the rhizomes. These findings regarding the quality and purity of the turmeric powder align with the findings of Abraham et al (2018), who reported an average ash content of 8.39% as an indicator of sample purity. Additionally, Zerihun et al (2017) reported a total ash content of 13.08% for rhizomes treated at 80°C for 30 minutes, while the lowest ash content of 9.95% was observed in rhizomes boiled at 100°C for 75 minutes.…”
Section: Total Ash (%)supporting
confidence: 87%
See 1 more Smart Citation
“…Increased boiling duration appears to have a greater impact on the total ash content in the rhizomes. These findings regarding the quality and purity of the turmeric powder align with the findings of Abraham et al (2018), who reported an average ash content of 8.39% as an indicator of sample purity. Additionally, Zerihun et al (2017) reported a total ash content of 13.08% for rhizomes treated at 80°C for 30 minutes, while the lowest ash content of 9.95% was observed in rhizomes boiled at 100°C for 75 minutes.…”
Section: Total Ash (%)supporting
confidence: 87%
“…Although native to southern India and Indonesia, turmeric cultivation has expanded to both mainland and island regions of the Indian Ocean. Turmeric rhizomes, characterized by their tough brown skin and bright orange flesh, possess distinctive pungent and bitter characteristics (Igbokwe et al, 2016;Abraham et al, 2018). In Nepal, the National Ginger Research Programme (NGRP) has released two commercial turmeric varieties, namely Kapurkot haledo-1 and Kapurkot haledo-2.…”
Section: Introductionmentioning
confidence: 99%